Zhejiang Semir Garment Co., Ltd. - McFarlan, F. Warren (SAGE knowledge. Cases., 2016)
Board chairman of Zhejiang Semir Garment Co. Qiu Guanghe attributes much of its success to its business model. Adopting the virtual production model, Semir Garment controls product design and brand building, but outsources production and logistics characterized by huge investment but relatively small profits to other companies. Its sales are done through chain stores and franchised outlets. This book evaluates the Zhejiang Semir Garment Co. model.